Financování developerského projektu - Pinnerová, Eliška (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce analyzuje financování developerského projektu Slunečný vrch, který je projektem společnosti ABILD s.r.o. Na základě podrobné analýzy projektu obsahuje návrhy podpory prodeje a jejich vliv na optimalizaci nákladů.

Master´s thesis analysed the financing of a development project Slunečný vrch, produced by ABILD s.r.o. company. On the basis of detailed analysis, the project includes proposals to support sales and optimize revenues.
Financing of a Development Project
Keywords: Developerský projekt; financování developerského projektu; bytová výstavba; marketing developerského projektu; podpora prodeje bytů; analýza nákladů na markting developerského projektu; náklady developerského projektu.; Development project; financing of a development project; housing construction; marketing of a development project; support sales of housing; cost analysis marketing of a development project; cost of a development project.